Perencanaan Sistem Penyaliran Tambang Batubara Dalam Perancangan Main Sump Block B PT Harmoni Panca Utama Jobsite PT Tambang Damai, Kalimantan Timur - Feraldo Sandrio; Rusli Har (Departemen Teknik Pertambangan FT UNP, 2023)
PT Harmoni Panca Utama jobsite Tambang Damai is a company engaged in the mining business with the type of mineral being mined is coal, which is located in East Kalimantan Province, East Kutai Regency. Mining operations carried out at PT Harmoni Panca Utama (HPU) jobsite PT Tambang Damai (TD) use the open pit method. This method will result information about potentional to become water catchment area, which is from ground water and run-off. The planned drainage system in the coal mining area of PT Harmoni Panca Utama is using combination metodhs there is mine drainage and mine dewatering, namely efforts to prevent, dry and remove water that enters the mining area. The mine drainage system plan is designed based on mining progress. Based on analysis of annual rainfall data, obtaining a planned rainfall of 117,67 mm/day. In the mine drainage system plan in the catchment area or catchment area with surface water runoff entering the mine opening of 20.74 m3 /s and a total groundwater discharge of 0.001 m3/s. In the main sump, there are 2 open channels or trapezoidal open channels. The sludge settling pond/settling pond is planned to be 4 compartments with a capacity of 1,500 m3 each.